Java 7 new features cookbook - Reese, Richard M., 1953- (Packt Pub., 2012)
Annotation Java 7 is a major update that includes a lot of exciting new language improvements such as support for type inference and improved exception handling. Other new features include the ability to work with symbolic links, a greatly simplified directory traversal technique, and the monitoring of file creation and deletion. Improvements in event handling, security, and concurrent processing have also been addedJava 7 New Features Cookbook is your go-to guide to learn about all the new exciting features Java 7 has to offer with a very practical recipe-based approach. The book starts with coverage of the new language improvements. Subsequent chapters address the new features of Java 7 while incorporating these new language improvements when possible. The new NIO techniques provide enhanced capabilities which are complemented by the new try-with-resources block and enhanced generic support. The new JLayer decorator and improved window methods enhance the developers ability to create GUI applications. The Java 7 New Features Cookbook provides a comprehensive coverage of the exciting features in Java 7.
Keywords: Java (Computer program language); elektronické knihy; electronic books